Pregnancy Outcomes Among Parturients Complicated with Diabetes Mellitus at Rajavithi Hospital - Ekachai Kovavisarach; Sutarat Srimaung (The Royal Thai College of Obstetricians and Gynaecologists, 2010)
Objective: To assess the prevalence, demographic characteristics, route of delivery, maternal and neonatal outcomes and complications of parturients complicated with diabetes mellitus (DM) at Rajavithi Hospital. Materials and Methods: Retrospective analysis of medical records of cases diagnosed pregnancy with DM from January 1, 2005 and September 30, 2007. Result: The prevalence of parturients complicated with DM was 1.84% of total deliveries. The most common maternal and neonatal complications were hypertensive disorders in pregnancy (25%) and macrosomia(33.6%), respectively. Occurrence of hypertensive disorder in pregnancy, macrosomia and neonatal hypoglycemia were significant difference between class A1, A2 and ³ B. Conclusion: The prevalence of parturients complicated with DM was 1.84% of total deliveries. The most common maternal and neonatal complications were hypertensive disorders complicating pregnancy and macrosomia.